Epigravettian Human Remains and Artifacts from Šandalja II, Istria, Croatia - Janković, Ivor (Array, 2012)
The Šandalja II site has yielded skeletal remains of at least three individuals found in association with numerous Late Upper Paleolithic (Epigravettian) stone tools and animal bones. It is the only Epigravettian site in Croatia that has yielded human remains. Analyses of the Šandalja discoveries add to our understanding of the morphological and behavioural patterns of the Late Upper Paleolithic inhabitants of this region. They provide us with a basis for comparison with not only contemporary humans of the Italian coastal region, which in the Late Pleistocene formed a single ecological zone with the Croatian coast, but also with Upper Paleolithic humans from other adjacent regions, which belonged to different ecological zones. Based on dental, cranial and postcranial metrics, the Šandalja II people were rather small compared to the comparative Upper Paleolithic samples and specimens. The associated late Epigravettian industry from the B/s layer of the site shows similarities in basic tool types with other comtemporaneous sites of the Adriatic region, while some noted differences are most likely a result of variation in site function. Continuing research on the Šandalja materials focuses on better understanding of morphological and behavioural variation, as well as contact patterns in the Late Upper Paleolithic of south Central Europe.